If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -2y = 17 Solving 6x + -2y = 17 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2y' to each side of the equation. 6x + -2y + 2y = 17 + 2y Combine like terms: -2y + 2y = 0 6x + 0 = 17 + 2y 6x = 17 + 2y Divide each side by '6'. x = 2.833333333 + 0.3333333333y Simplifying x = 2.833333333 + 0.3333333333y
| -1+x/4=5 | | x^2+8x-2y+6=0 | | -t/2=1/2 | | 12+7x=3x | | 3x-6x=16 | | 68,09=-189,7/x | | (4-3)m=-1 | | (-p^5q^4)+(4p^5q^4)= | | 5,305/x=11,65 | | 7x-8(x+3)=2 | | 13/6x=1/10-10/9 | | 3x=-4x-14 | | 11=v/25+12 | | Y=-143.3(64)+1823.3(8)+6820 | | 50-3x=9-8x | | -32+5x=26 | | (6v-9)/3 | | F(x)=2x^2-4x-1 | | 3x-(x+6)=16 | | 7(w-5)=-5w+1 | | 3k+4=28 | | 2/3x=-4/27 | | K=mc^2 | | 66=-15x+6 | | 114/12 | | X/12+5/6=5/24 | | 2x+(45x-14)=1-x | | -3x+40=x^2 | | -m/4=-3/4 | | 6(w-3)-8w=-16 | | -143.3(10)(10)+1823.3(10)+6820= | | 49*7/6 |